The relationship between mantle pH and the deep nitrogen cycle. (15th July 2017) - Mikhail, Sami; Barry, Peter H.; Sverjensky, Dimitri A.
Abstract: Nitrogen is distributed throughout all terrestrial geological reservoirs (i.e., the crust, mantle, and core), which are in a constant state of disequilibrium due to metabolic factors at Earth's surface, chemical weathering, diffusion, and deep N fluxes imposed by plate tectonics. However, the behavior of nitrogen during subduction is the subject of ongoing debate. There is a general consensus that during the crystallization of minerals from melts, monatomic nitrogen behaves like argon (highly incompatible) and ammonium behaves like potassium and rubidium (which are relatively less incompatible). Therefore, the behavior of nitrogen is fundamentally underpinned by its chemical speciation. In aqueous fluids, the controlling factor which determines if nitrogen is molecular (N2 ) or ammonic (inclusive of both NH4 + and NH3 0 ) is oxygen fugacity, whereas pH designates if ammonic nitrogen is NH4 + or NH3 0 . Therefore, to address the speciation of nitrogen at high pressures and temperatures, one must also consider pH at the respective pressure–temperature conditions. To accomplish this goal we have used the Deep Earth Water Model (DEW) to calculate the activities of aqueous nitrogen from 1–5 GPa and 600–1000 °C in equilibrium with a model eclogite-facies mineral assemblage of jadeite + kyanite + quartz/coesite (metasediment), jadeite + pyrope + talc + quartz/coesite (metamorphosed mafic rocks), and carbonaceous eclogite (metamorphosed mafic rocks + elemental carbon). We then compare these data with previously published data for the speciation of aqueous nitrogen across these respective P-T conditions in equilibrium with a model peridotite mineral assemblage (Mikhail and Sverjensky, 2014). In addition, we have carried out full aqueous speciation and solubility calculations for the more complex fluids in equilibrium with jadeite + pyrope + kyanite + diamond, and for fluids in equilibrium with forsterite + enstatite + pyrope + diamond. Our results show that the pH of the fluid is controlled by mineralogy for a given pressure and temperature, and that pH can vary by several units in the pressure-temperature range of 1–5 GPa and 600–1000 °C. Our data show that increasing temperature stabilizes molecular nitrogen and increasing pressure stabilizes ammonic nitrogen. Our model also predicts a stark difference for the dominance of ammonic vs. molecular and ammonium vs. ammonia for aqueous nitrogen in equilibrium with eclogite-facies and peridotite mineralogies, and as a function of the total dissolved nitrogen in the aqueous fluid where lower N concentrations favor aqueous ammonic nitrogen stabilization and higher N concentrations favor aqueous N2 . Overall, we present thermodynamic evidence for nitrogen to be reconsidered as an extremely dynamic (chameleon) element whose speciation and therefore behavior is determined by a combination of temperature, pressure, oxygen fugacity, chemical activity, and pH. We show that altering the mineralogy in equilibrium with the fluid can lead to a pH shift of up to 4 units at 5 GPa and 1000 °C. Therefore, we conclude that pH imparts a strong control on nitrogen speciation, and thus N flux, and should be considered a significant factor in high temperature geochemical modeling in the future. Finally, our modelling demonstrates that pH plays an important role in controlling speciation, and thus mass transport, of Eh-pH sensitive elements at temperatures up to at least 1000 °C.